Exploiting the anti-fibrotic effects of statins on thoracic aortic aneurysm progression: results from a meta-analysis and experimental data - Myasoedova, Veronika A.; Rega, Sara; Valerio, Vincenza; Moschetta, Donato; Massaiu, Ilaria; Bonalumi, Giorgia; Esposito, Giampiero; Rusconi, Valentina; Bertolini, Francesca; Perrucci, Gianluca Lorenzo; Poggio, Paolo (Frontiers in Pharmacology, 2024)
Aims: Thoracic aortic aneurysm (TAA) that progress to acute aortic dissection is often fatal and there is no pharmacological treatment that can reduce TAA progression. We aim to evaluate statins' effects on TAA growth rate and outcomes using a meta-analysis approach.A detailed search related to the effects of statins on TAA was conducted according to PRISMA guidelines. The analyses of statins' effects on TAA growth rate were performed on 4 studies (n=1850), while the impact on outcomes was evaluated on 3 studies (n=2867).Patients under statin treatment showed a reduced TAA growth rate (difference in means=-0.36 cm/year; 95%CI: -0.64, -0.08; p=0.013) when compared to controls, patients not taking statins.Regarding the outcomes (death, dissection, or rupture of the aorta, and the need for operative repair), statins exhibited a protective effect reducing the number of events (log odds ratio=-0.56; 95%CI: -1.06, -0.05; p=0.030). In vitro, the anti-fibrotic effect of atorvastatin was tested on vascular smooth muscle cells (VMSC) isolated from patients with TAA. Our results highlighted that, in transforming growth factor beta 1 (TGF-β1) pro-fibrotic condition, VSMC expressed a significant lower amount of collagen type I alpha 1 chain (COL1A1) when treated with atorvastatin (untreated=+2.66±0.23 fold-change vs. treated=+1.63±0.09 fold-change; p=0.014).Statins show a protective effect on TAA growth rate and adverse outcomes in patients with TAA, possibly via their anti-fibrotic properties on VSMC. Given the current lack of effective drug treatments for TAA, we believe our findings highlight the need for more in-depth research to explore the potential benefits of statins in this context.